المعرفة النظرية والأداء التطبيقي لأحكام المد في القرآن الكريم: دراسة ميدانية لمعلمات التربية الإسلامية بمحافظة شمال الباطنة: Theoretical Knowledge and Practical Performance of Qur’anic Elongation Rules: Field Study of Islamic Education Teachers in North Al Batinah Governorate - Salim Al Saadiyah , Sheikha Masoud; Ramadan, Tahraoui (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث سعت الدراسة الحالية إلى الكشف عن مستوى المعرفة النظرية والأداء التطبيقي في أحكام المد لدى معلمات التربية الإسلامية بالحلقة الثانية في محافظة شمال الباطنة. وللمساعدة في تحقيق أهداف البحث استخدم الباحثان المنهج الوصفي التقويمي لمناسبته لهذه النوع من البحوث. وقد تمثل مجتمع الدراسة في جميع معلمات الحلقة الثانية لمادة التربية الإسلامية بمحافظة شمال الباطنة بسلطنة عمان، أما العينة فقد تمثلت في (24) معلمة، تم اختيارهن بالطريقة العشوائية الطبقية. ولجمع بيانات الدراسة أعد الباحثان أداتي بحث هما: الاختبار التحصيلي، والاختبار العملي التطبيقي. وقد توصلت الدراسة إلى أن مستوى أداء المعلمات في المعرفة النظرية والأداء التطبيقي لأحكام المد كان أقل من مستوى التمكن (90%)؛ إذ بلغ المتوسط الحسابي لكلاهما على التوالي (69.44%(، (70.88%)، كما كشفت النتائج أن مستوى أداء العينة في التطبيق العملي لأحكام المد عاليا في تطبيق ثلاثة أنواع من المدود هي: مد العوض، والمد الطبيعي، ومد البدل، ومتوسطا في ثلاثة أنواع أخرى من المدود هي: مد الصلة الكبرى، والمد الجائز المنفصل، ومد الصلة الصغرى، في حين كان الأداء منخفضا في تطبيق خمسة أنواع من المد هي: المد الواجب المتصل، والمد العارض للسكون، والمد اللازم الحرفي، ومد اللين، والمد اللازم الكلمي. وقد أوصت الدراسة بعقد برامج تدريبية بصورة مستمرة؛ من أجل تحسين كفايات التلاوة في أحكام تجويد المد، مع وجود التغذية الراجعة الفاعلة في التدريب، وإبراز دور الإشراف الفني في تمكين المعلمات من التطبيق العملي لأحكام التجويد، ومنها أحكام المد من خلال ورش العمل والمشاغل التربوية، واستهداف حصة التلاوة في الزيارات الإشرافية لتحقيق المزيد من التطوير. ABSTRACT The present study aimed to examine the level of theoretical knowledge and practical application of the rules of madd (elongation) among Islamic education teachers in the second cycle of basic education in North Al Batinah Governorate. The researchers employed a descriptive evaluative approach to achieve the study’s objectives. The research sample consisted of 24 teachers, selected through stratified random sampling method. To collect data, the researchers developed two research instruments: Achievement Test and Practical Performance Test. The findings revealed that teachers’ performance in both theoretical knowledge and practical application of madd rules was below the mastery level (90%). The mean scores for theoretical knowledge and practical application were 69.44% and 70.88%, respectively. The results revealed in a high level of performance in the application of three types of madd: Replacement Elongation (madd ewad), Natural Elongation (madd tabiee), and Exchange Elongation (madd badal). The performance was average in three types of tide, namely: The Bigger connecting Elongation (madd al-silah al-kubra),The Separated Elongation (madd munfasil), The smaller Elongation (madd al-silah al-sughra), while performance was low in applying five types of tide, namely: The connected Elongation (madd muttasil), The Ending Elongation (madd ’arid lil-sukun), The Required Elongation (madd lazim harfy),The Soft Elongation (madd al-leen), The Required Elongation (madd lazim kalimy). The results of the research recommended holding more frequent training programs aimed at improving the competencies of recitation, and careful considerations to participants’ feedbacks.